Evaluasi Kegiatan Pengabdian kepada Masyarakat Dosen Universitas Lancang Kuning - Refika Andriani; Maratul Afidah (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
This research aims at describing the process of community service program implemented by the lecturers of Education and Teachers Training Faculty of Universitas Lancang Kuning using Context, Input, Process, dan Product (CIPP). The method of the research is descriptive analysis with no actions, manipulation or changed the data of independent variables. It truly describes the result of evaluation of the Community Service Program Implemented by the lecturers of Teachers Training Faculty of Universitas Lancang Kuning using Context, Input, Process, dan Product (CIPP). The instrument used for collecting the data is questionnaire. It was given to the lecturers who implemented the program in Academic Year 2017/2018. Based on the data analyzing, it was found that the achievement of Community Service Program Implementation was 80 %, categorized into good. Then, the result of this research is expected can be a reference for deciding and implementing a particular method and procedure relates to quality improvement of Community Service Program Implementation handle by lecturers of Education and Teachers Training Faculty of Universitas Lancang Kuning.